2002
DOI: 10.1161/01.atv.0000023428.69244.49
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Inhibits Expression of p21(WAF1/CIP1) and p27(KIP1) and Enhances Proliferation in Response to Platelet-Derived Growth Factor-BB in Smooth Muscle Cells

Abstract: Objective-Intimal growth depends on smooth muscle cell (SMC) migration and proliferation and is regulated by thrombotic and inflammatory responses to vascular injury. Platelet-derived growth factor (PDGF)-BB and interleukin (IL)-1␤ have been shown to contribute to intimal hyperplasia and lesion progression in atherosclerosis. Mitogenic effects of IL-1 on SMCs have been reported and have been attributed to the expression of PDGF-A chain. In some, but not all, studies, IL-1␤ was found to cooperate with growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…1A, lane 2) after 8 hours. Enhancement of the activity of CDK2 by IL-1h has been reported before (19). We therefore explored the possibility that IL-1h-induced COX-2 expression may involve CDK2.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1A, lane 2) after 8 hours. Enhancement of the activity of CDK2 by IL-1h has been reported before (19). We therefore explored the possibility that IL-1h-induced COX-2 expression may involve CDK2.…”
Section: Resultsmentioning
confidence: 92%
“…Induction of COX-2 expression by IL-1h operates at the transcriptional level involving transcription factors, such as nuclear factor-nB (NF-nB) and CCAAT/enhancer-binding protein (C/EBP), as well as at the level of mRNA stabilization in a extracellular signal-regulated kinase 1/2 (ERK1/2)-dependent process (17,18). Interestingly, IL-1h also enhances the activity of the CDK2 (19). We therefore investigated whether IL-1h-induced COX-2 expression involves CDK2.…”
Section: Introductionmentioning
confidence: 99%
“…2 In recent years, accumulating evidence has implicated various CKIs as important endogenous regulators of leukocyte and VSMCs proliferation in various pathophysiological situations. [3][4][5] The regulation of CKI expression/activity influences the response of VSMCs to mechanical stimuli (such as blood flow) and to molecules (such as nitric oxide, interleukines, angiotensin II and growth factors), and is mediated through the regulation of CKI expression/activity. [6][7][8][9][10] For example, reduced expression of p27 has been reported in primary atherosclerotic and restenotic tissue versus nondiseased arterial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…These EC data contrast with the role of IL-1 in VSMCs, where IL-1 enhances platelet-derived growth factor-BB (PDGF-BB) cell proliferation, an effect mediated by increased CDK2 activity [10]. Administration of IL1ra to these cells inhibits VSMC proliferation whilst IL-1ra in combination with PDGF-BB enhances proliferation [10].…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have suggested a role for G1 cell cycle proteins in the IL-1 mediated proliferation of vascular smooth muscle cells [10] and the senescence of ECs [11]. Cyclin dependent kinase-2 (CDK2) activity is diminished in senescent HUVEC whilst bypassing senescence with telomerase restores CDK2 translation and activity [11].…”
Section: Introductionmentioning
confidence: 99%